Medicinal plant knowledge in a context of cultural pluralism: a case study in Northeastern Brazil - Abreu, Diego Batista de Oliveira (2015)
Ethnopharmacological relevance The study of plant use in contexts of migrations can give important insights to cultural evolution, since people face rapid changes in their environments and often start interacting with native dwellers, both constituting forces that can lead to change. Therefore, this study focused on medicinal plant knowledge and transmission in order to understand what happens to such knowledge when people from several regions converge to a single place already inhabited by native people. Methods The study was carried out in the rural community of Caeté-Açu (known as Capão Valley), placed in the state of Bahia (NE Brazil). Native and migrant people's knowledge on medicinal plans was accessed with a free listing. People were also asked about whom in the community once taught them about medicinal plants. Four groups (native, regional migrants, national migrants and international migrants) were compared in terms of number of cited plants, plant repertoires and knowledge transmission. For each group we also ran simple regressions between age and number of cited plants and residence time and number of cited plants. Results and discussion We found no differences among groups in terms of number of known species. However, plant repertoires differ in some extent among groups. While migrants claim to have learnt with both native people and other migrants, most native claim to have learned mainly with other natives. Age influences plant knowledge only for the natives, what strengthens evidence that this group's knowledge is based on experience while migrants'’ knowledge is based on an active search. Residence time in the community did not influence migrants’ knowledge. Conclusion Native and migrant people have differences in their ways of acquiring medicinal plant knowledge and less popular species are also different between groups. However, we can observe a tendency of fusion and indissolubility of migrant and native knowledge since the new generations are in contact with both sources.